Kyai dan Jawara Banten: Keislaman, Kepemimpinan dan Magic - H. M.A Tihami (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2015)
This article tries to describe kiyai’s and jawara’s leadership inBanten. Kiyai and jawara are prominent figures, who become a symbol ofidentity of Banten, which is well known a religious region and a “countryof ‘ulamā’ and jawara.” The role and position of kiyai and jawara areimportant since the era of Kasultanan Banten until nowadays. Kiyai, withhis religious knowledge and magic competence (acquired from religoussources), serves people as an informal leader. While jawara, because of hiscourage and magic competence (obtained from kiyai), becomes a secondinformal leader after kiyai.